2002
DOI: 10.1002/pits.10044
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of school psychologists for crisis intervention

Abstract: School psychologists (N ϭ 276, 81% return rate) were surveyed regarding the following aspects of crisis intervention: (a) university preparation, (b) continuing professional development, and (c) current involvement with school crisis plans and crisis teams. Of those receiving university training, 58% believed they were minimally prepared or not at all prepared to deal with school crises. Only 2% reported being well prepared or very well prepared. Data analyses indicated increased university training in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 14 publications
9
48
1
1
Order By: Relevance
“…Results indicated that only 8% had completed a course specific to crisis intervention and 55% had received crisis intervention information as one of many topics covered elsewhere within their training. Similarly, Allen et al's (2002) survey of 276 National Certified School Psychologists found that school psychologists perceived crisis training as important, yet only 5% of respondents had completed a specific course in crisis intervention. Despite this lack of training, recent surveys have indicated that about half of school psychologists are active members of school crisis teams (Allen et al;Bramlett et al, 2002).…”
Section: Role Of School Psychologistsmentioning
confidence: 95%
See 2 more Smart Citations
“…Results indicated that only 8% had completed a course specific to crisis intervention and 55% had received crisis intervention information as one of many topics covered elsewhere within their training. Similarly, Allen et al's (2002) survey of 276 National Certified School Psychologists found that school psychologists perceived crisis training as important, yet only 5% of respondents had completed a specific course in crisis intervention. Despite this lack of training, recent surveys have indicated that about half of school psychologists are active members of school crisis teams (Allen et al;Bramlett et al, 2002).…”
Section: Role Of School Psychologistsmentioning
confidence: 95%
“…These findings mirror the recommendations in the crisis intervention literature, in which the crisis response team is the hallmark (Brock et al, 2001;Pitcher & Poland, 1992). Although other studies have assessed school psychologists' involvement in these teams (Allen et al, 2002;Bramlett et al, 2002), there is no research about the perceived effectiveness of these teams. It is noteworthy that school psychologists in this study perceived the crisis response team to be the most effective crisis preparation strategy.…”
Section: Crisis Prevention and Intervention Strategiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Intervention with a potentially suicidal student thus appears to be one of the more frequently encountered crisis situations experienced by school psychology practitioners (Allen et al, 2002;Nickerson & Zhe, 2004). Consequently, school psychologists need to be knowledgeable of the risk factors for youth suicide, warning signs and precipitating events, methods to conduct a suicide risk assessment, recommended actions in low-and high-risk situations, and appropriate school responses in the aftermath of a student suicide (Brent & Perper, 1995;Lieberman & Davis, 2002;Poland & Lieberman, 2002).…”
mentioning
confidence: 98%
“…Recent surveys of school psychologists provide evidence that crisis response teams are prevalent in schools, with 93% of respondents in Nickerson and Zhe's (2004) study indicating that their schools used these teams and 76% of respondents in Allen et al's (2002) study reporting that their districts had these teams. However, Graham, Shirm, Liggen, Aitken, and Dick's (2006) recent study of school superintendents revealed deficiencies in school emergency/disaster planning.…”
Section: School Crisis Teamsmentioning
confidence: 99%